Liver Cancer Emergence Associated with Antiviral Treatment: An Immune Surveillance Failure? - Reig, María; Boix, Loreto; Mariño, Zoe; Torres, Ferran; Forns, Xavier; Bruix, Jordi (Seminars in Liver Disease, 2017)
The availability of new direct antiviral agents to safely and effectively treat the hepatitis C virus represents a major advancement in the field of liver disease. Most patients achieve complete viral eradication sustained over time. In addition, the administration of these new agents is safe and does not require limitations when liver function is impaired. Some now expect the hepatitis C virus to be completely eradicated in a few years. However, not all data are positive. In April 2016, we published a cohort study suggesting that viral eradication with the new agents could be associated in time with the emergence of recurrent cancer sites in patients previously treated for hepatocellular carcinoma. In this review, we update our report and summarize the data provided in recent publications. We also speculate about the mechanisms for cancer emergence and stress the need for further studies.
Keywords: hepatitis C; hepatocellular carcinoma; direct antiviral agents; incidence; recurrence